Population estimates of obstructive and non-obstructive hypertrophic cardiomyopathy in the UK and Germany. (3rd October 2022) - Schultze, M; Zema, C; Carroll, R; Hurst, M; Borchert, J; Zhong, Y; Krause, T; Bluhmki, T; Partington, H; Osman, F; Tome Esteban, M
Abstract: Background: While numerous publications have estimated the prevalence of diagnosed hypertrophic cardiomyopathy (HCM), none have quantified the real-world proportion of obstructive and non-obstructive HCM using nationally representative data sources in any European countries. Purpose: To estimate the prevalence of diagnosed HCM and its subtypes in the UK and Germany. Methods: Patients with HCM were identified in the UK from 01 Apr 2009 to 30 Oct 2020 and Germany from 2011 to 2019. UK patients with HCM were identified using electronic health records from the Clinical Practice Research Datalink (CPRD) primary care data linked with Hospital Episode Statistics (HES) secondary care data using ICD-10 (I42.1, I42.2), Read, Medcode, SNOMED, and OPCS codes. German patients with HCM were identified using a nationally representative administrative claims data pool (WIG2 Benchmark database) from several German Statutory Health Insurance (SHI)-insurances using ICD-10 and OPS codes. Obstructive HCM was identified as any obstructive HCM diagnosis, any HCM diagnosis with septal reduction therapy, and any HCM diagnosis and left ventricular outflow tract obstruction (LVOTO; not in German claims data). Non-obstructive HCM was any non-obstructive or unspecified HCM diagnosis without evidence of any obstructive HCM. Annual prevalence was calculated for each year in the respective study periods and average annual prevalence across the study period. Results: The average annual prevalence rate of HCM was 4.15/10, 000 in the UK and 8.61/10, 000 in Germany, while the average annual prevalence rate of obstructive HCM was 2.84/10, 000 in the UK and 4.18/10, 000 in Germany (Table). The proportion of HCM that was obstructive HCM was 68% in the UK and 49% in Germany. The prevalence rates of diagnosed HCM and obstructive HCM tended to increase over time (Figure). Conclusion: The prevalence of HCM, obstructive HCM and the proportion of HCM that is obstructive varied between the UK and Germany. The prevalence of HCM was generally consistent with previously published estimates. Although there are limitations with coding in administrative data, it is important to differentiate obstructive HCM from non-obstructive HCM given their unique treatments and disease progression and management, especially since at least 49–68% of HCM is obstructive. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Bristol Myers-Squibb